Association of phthalate exposure with type 2 diabetes and the mediating effect of oxidative stress: A case-control and computational toxicology study - Yuxuan Tan; Ziang Guo; Huojie Yao; Han Liu; Yingyin Fu; Yangxu Luo; Rong He; Yiwan Liu; Pei Li; Lihong Nie; Lei Tan; Chunxia Jing (Ecotoxicology and Environmental Safety, 2024)
Phthalic acid esters (PAEs) are widely used as plasticizers and have been suggested to engender adverse effects on glucose metabolism. However, epidemiological data regarding the PAE mixture on type 2 diabetes (T2DM), as well as the mediating role of oxidative stress are scarce. This case-control study enrolled 206 T2DM cases and 206 matched controls in Guangdong Province, southern China. The concentrations of eleven phthalate metabolites (mPAEs) and the oxidative stress biomarker 8-hydroxy-2′-deoxyguanosine (8-OHdG) in urine were determined. Additionally, biomarkers of T2DM in paired serum were measured to assess glycemic status and levels of insulin resistance. Significantly positive associations were observed for mono-(2-ethylhexyl) phthalate (MEHP) and Mono(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP) with T2DM (P < 0.001). Restricted cubic spline modeling revealed a non-linear dose-response relationship between MEHHP and T2DM (Pnon-linear = 0.001). The Bayesian kernel machine regression and quantile g-computation analyses demonstrated a significant positive joint effect of PAE exposure on T2DM risk, with MEHHP being the most significant contributor. The mediation analysis revealed marginal evidence that oxidative stress mediated the association between the mPAEs mixture and T2DM, while 8-OHdG respectively mediated 26.88 % and 12.24 % of MEHP and MEHHP on T2DM risk individually (Pmediation < 0.05). Di(2-ethylhexyl) phthalate (DEHP, the parent compound for MEHP and MEHHP) was used to further examine the potential molecular mechanisms by in silico analysis. Oxidative stress may be crucial in the link between DEHP and T2DM, particularly in the reactive oxygen species metabolic process and glucose import/metabolism. Molecular simulation docking experiments further demonstrated the core role of Peroxisome Proliferator Activated Receptor alpha (PPARα) among the DEHP-induced T2DM. These findings suggest that PAE exposure can alter oxidative stress via PPARα, thereby increasing T2DM risk.